Sistem Pakar Diagnosis Penyakit Ginjal Dengan Menggunakan Metode Dempster Shafer - Suherman Suherman; Zaenur Rozikin (Jurnal SIGMA, 2019)
Expert systems are computer-based systems that use knowledge, facts, and reasoning in solving problems that are usually only solved by an expert in a particular field. Expert systems provide added value to technology to help deal with an increasingly sophisticated information age. This expert system application produces an output in the form of the possibility of kidney disease suffered based on symptoms felt by the user. This system also displays the magnitude of the symptom's belief in the possibility of kidney disease suffered by the user. The amount of the trust value is the result of calculations using the Dempster Shafer method. Keywords : Kidney, Expert System, Dempster-Shafer Method